Grow the pie : how great companies deliver both purpose and profit - Edmans, Alex, 1980- (Cambridge University Press, 2022)
"What is a responsible business? Common wisdom is that it's one that sacrifices profit for social outcomes. But while it's crucial for companies to serve society, they also have a duty to generate profit for investors - savers, retirees, and pension funds. Based on the highest-quality evidence and real-life examples spanning industries and countries, Alex Edmans shows that it's not an either-or choice - companies can create both profit and social value. The most successful companies don't target profit directly, but are driven by purpose - the desire to serve a societal need and contribute to human betterment. The book explains how to embed purpose into practice so that it's more than just a mission statement, and discusses the critical role of working collaboratively with a company's investors, employees, and customers. Rigorous research also uncovers surprising results on how executive pay, shareholder activism, and share buybacks can be used for the common good."--Nakladatelská anotace